Age Related Response of Neonatal Rat Retinal Ganglion Cells to Reduced TrkB Signaling in vitro and in vivo - Beros, Jamie; Rodger, Jennifer; Harvey, Alan R (Frontiers in Cell and Developmental Biology, 2021)
During development of retinofugal pathways there is naturally occurring cell death of at least 50% of retinal ganglion cells (RGCs). In rats, RGC death occurs over a protracted pre- and early postnatal period, the timing linked to the onset of axonal ingrowth into central visual targets. Gene expression studies suggest that developing RGCs switch from local to target-derived neurotrophic support during this innervation phase. Here we investigated, in vitro and in vivo, how RGC birthdate affects the timing of the transition from intra-retinal to target-derived neurotrophin dependence. RGCs were pre-labeled with 5-Bromo-2′-Deoxyuridine (BrdU) at embryonic (E) day 15 or 18. For in vitro studies, RGCs were purified from postnatal day 1 (P1) rat pups and cultured with or without: (i) brain derived neurotrophic factor (BDNF), (ii) blocking antibodies to BDNF and neurotrophin 4/5 (NT-4/5), or (iii) a tropomyosin receptor kinase B fusion protein (TrkB-Fc). RGC viability was quantified 24 and 48 h after plating. By 48 h, the survival of purified βIII-tubulin immunopositive E15 but not E18 RGCs was dependent on addition of BDNF to the culture medium. For E18 RGCs, in the absence of exogenous BDNF, addition of blocking antibodies or TrkB-Fc reduced RGC viability at both 24 and 48 h by 25–40%. While this decrease was not significant due to high variance, importantly, each blocking method also consistently reduced complex process expression in surviving RGCs. In vivo, survival of BrdU and Brn3a co-labeled E15 or E18 RGCs was quantified in rats 24 h after P1 or P5 injection into the eye or contralateral superior colliculus (SC) of BDNF and NT-4/5 antibodies, or serum vehicle. The density of E15 RGCs 24 h after P1 or P5 injection of blocking antibodies was reduced after SC but not intraretinal injection. Antibody injections into either site had little obvious impact on viability of the substantially smaller population of E18 RGCs. In summary, most early postnatal RGC death in the rat involves the elimination of early-born RGCs with their survival primarily dependent upon the availability of target derived BDNF during this time. In contrast, late-born RGC survival may be influenced by additional factors, suggesting an association between RGC birthdate and developmental death mechanisms.